PENGARUH KARAKTERISTIK PEMERINTAH DAERAH DAN HASIL PEMERIKSAAN AUDIT BPK TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Satriawaty Migang; Ummi Latifatuz Zahro (Fakultas Ekonomi Universitas Pekalongan, 2020)
This study aims to determine the effect of the local government characteristics and audit opinion on the financial performance of local governments in all urban districts in East Kalimantan. The samples used were as many as 10 districts / cities using purposive sampling method. Data were collected by using the method of documentation. Analysis of the data used in this research is multiple regression analysis with signification at 5%. The results showed partially (t test) that the variable Regional Wealth Levels, and BPK Audit Findings had an effect on financial performance, while Regional Expenditures and Dependency Levels on the Center had no effect on the financial performance of the Regional Government. While simultaneously (F test) that the variable level of regional wealth, regional expenditure, level of dependence with the center and BPK audit findings have a significant effect on Local Government Financial Performance. Keywords: financial performance, regional level, regional expenditure, level of freedom at the center, and opinion audit